Blue Skies research is essential for ending the Tuberculosis pandemic and advancing a personalized medicine approach for holistic management of Respiratory Tract infections. (November 2022) - Ntoumi, Francine; Petersen, Eskild; Mwaba, Peter; Aklillu, Eleni; Mfinanga, Sayoki; Yeboah-Manu, Dorothy; Maeurer, Markus; Zumla, Alimuddin
Highlights: 'Blue skies research' refers to basic science or fundamental research 'Blue skies research' is essential new TB tools development for eradicating TB Investments into fundamental TB research in LMICs is long overdue COVID-19 advances bring hope for more holistic care for all RTIs ABSTRACT: Objectives: Investments into 'Blue Skies' fundamental TB research in low- and middle-income countries (LMICs) have not been forthcoming. We highlight why blue skies research will be essential for achieving global TB control and eradicating TB. Methods: We review the historical background to early TB discovery research and give examples of where investments into basic science and fundamental 'blue skies research' are delivering novel data and approaches to advance diagnosis, management and holistic care for patients with active and latent TB infection. Findings: The COVID-19 pandemic has shown that making available adequate funding for priority investments into 'Blue skies research' to delineate scientific understanding of a new infectious diseases threat to global health security can lead to rapid development and rollout of new diagnostic platforms, treatments, and vaccines. Several advances in new TB diagnostics, new treatments and vaccine development are underpinned by basic science research. Conclusions: Blue Skies research is required to pave the way for a personalized medicine approach for management of TB and other Respiratory Tract Infections and preventing long-term functional disability. Transfer of skills and resources by wealthier nations is required to empower researchers in LMICs countries to engage in and lead Blue Skies research.